2012
DOI: 10.1016/j.energy.2011.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Experimental real-time optimization of a solid oxide fuel cell stack via constraint adaptation

Abstract: a b s t r a c tThe experimental validation of a real-time optimization (RTO) strategy for the optimal operation of a solid oxide fuel cell (SOFC) stack is reported in this paper. Unlike many existing studies, the RTO approach presented here utilizes the constraint-adaptation methodology, which assumes that the optimal operating point lies on a set of active constraints and then seeks to satisfy those constraints in practice via the addition of a correction term to each constraint function. These correction ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 16 publications
2
48
0
1
Order By: Relevance
“…On the other hand, thermal equilibration is much slower. The fast RTO approach in [53] is very simple and uses CA. The RTO period is set somewhere between the time scale of the electrochemical reaction and the time scale of the thermal process.…”
Section: Use Of Transient Measurements For Mamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, thermal equilibration is much slower. The fast RTO approach in [53] is very simple and uses CA. The RTO period is set somewhere between the time scale of the electrochemical reaction and the time scale of the thermal process.…”
Section: Use Of Transient Measurements For Mamentioning
confidence: 99%
“…The concept of fast RTO via CA was introduced and applied to an experimental solid oxide fuel-cell stack in the presence of operating constraints and plant-model mismatch [53]. Solid oxide fuel-cell stacks are, roughly speaking, electrochemical reactors embedded in a furnace.…”
Section: Use Of Transient Measurements For Mamentioning
confidence: 99%
“…Although this worked sometimes, it also led to significant "large misses" when the CAES storage volume reached minimum or maximum capacity, leading to all flexibility in the system being lost instantaneously [11]- [13]. The concept of real-time optimization [16]- [19] being used in chemical plants and even with small SOFC experimental setups [20] led to the eventual development of a rolling horizon optimization (RHO) technique that uses forecasts of future demand to optimally plan the next series of control moves based on the operating and storage constraints of the SOFC/CAES system [21]. With this approach, the system would predict a potential problem and then avoid it by scheduling a series of "small misses" over time in order to prevent a more serious large miss.…”
Section: Introductionmentioning
confidence: 99%
“…As the stack temperature has been recognized to have significant impacts on the cell lifespan, some studies have improved the constant temperature model by including the energy balance equation. It was reported in [29][30][31] that the temperature can be maintained within a safe range by regulating the air flow rate. Vijay et al [30] showed that the response of the stack temperature is in the order of several minutes when the stack current has a step change.…”
Section: Introductionmentioning
confidence: 99%